Hydrogeology : objectives, methods, applications. - Gilli, Eric, ....-; Mangan, Christian, ....-; Mudry, Jacques, ....- (Boca Raton : CRC, 2013)
Hydrogeology, the science of groundwater, requires a multidisciplinary approach involving many other sciences: surface hydrology, climatology, geology, geography, physics, chemistry, biology, and more. This book takes a broad view, considers water as a single entity, and presents many examples illustrating the variety of existing hydrogeological problems and the diverse scientific, technical, and social approaches used in resolving them. It is intended primarily for students of Earth Sciences, Environmental Sciences, and Physical Geography. It will also be useful to all players involved in water-related issues: hydrogeologists, geologists, soil scientists, agronomists, civil engineers, and developers.